Measurement of D0-D [bar] 0 mixing parameters using D0→K0Sπ+π− and D0→K0SK+K- decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review letters, 2010)
We report a direct measurement of D0−¯¯¯D0 mixing parameters through a time-dependent amplitude analysis of the Dalitz plots of D0→K0Sπ+π− and, for the first time, D0→K0SK+K− decays. The low-momentum pion π+s in the decay D*+→D0π+s identifies the flavor of the neutral D meson at its production. Using 468.5 fb−1 of e+e− colliding-beam data recorded near √s=10.6 GeV by the BABAR detector at the PEP-II asymmetric-energy collider at SLAC, we measure the mixing parameters x=[1.6±2.3(stat)±1.2(syst)±0.8(model)]×10−3, and y=[5.7±2.0(stat)±1.3(syst)±0.7(model)]×10−3. These results provide the best measurement to date of x and y. The knowledge of the value of x, in particular, is crucial for understanding the origin of mixing.